P222 Manipulation of connectivity in the dorsal attention network and its effects on attentional control. Issue 3 (March 2017) - Duecker, F.; Schilberg, L.; Sack, A.
Abstract : Introduction: Attention allows prioritizing those aspects of incoming sensory information that are most relevant to us. Functional-anatomical models of attentional control emphasize the role of the dorsal attention network (DAN), consisting of the frontal eye field (FEF) and intraparietal sulcus (IPS). The DAN is widely accepted to mediate attention shifts but the functional organization within the DAN remains poorly understood, in particular the functional relevance of its complex connectivity patterns. Objectives: We set out to manipulate connectivity within the right DAN using paired associative stimulation (PAS), thus experimentally assessing the functional relevance of connectivity within the DAN for attentional control. PAS is a novel brain stimulation approach that involves the repeated application of transcranial magnetic stimulation pulses with two coils targeting two interconnected brain areas that has recently been established in the motor system and is here pioneered in the cognitive domain. Methods: Nine participants first took part in an fMRI session to identify individual brain activation foci of right FEF and right IPS. Then, PAS was applied to these brain regions in two sessions for 15 min at 0.1 Hz followed by a spatial orienting paradigm requiring endogenous shifts of attention (valid, neutral, and invalid trials). Critically, in the experimental condition a TMS pulse over FEF preceded a TMS pulse over IPS by 8 ms (leading to neuroplasticity due to simultaneous activation of both brain areas) whereas this interval was extended to 500 ms in our control condition (no neuroplasticity). Results: PAS over the right DAN differentially affected attentional performance in a hemifield-specific way. Specifically, attentional benefits were unaffected by PAS in both hemifields whereas attentional costs were significantly increased in the left hemifield only. Conclusion: We demonstrate that PAS over the right DAN has differential effects on attentional control processes, strongly suggesting that PAS is capable of manipulating connectivity outside the human motor cortex. While the specific pattern of results is somewhat unexpected (no effects on attention benefits), the present experiment is a first step towards unravelling the functional relevance of connectivity in cognitive brain networks.